Temporal dynamics and compartment specific rice straw degradation in bulk soil and the rhizosphere of maize - Maarastawi, Sarah A.; Frindte, Katharina; Geer, Romy; Kröber, Eileen; Knief, Claudia (Soil biology & biochemistry, 2018)
Crop rotation between paddy rice and maize is of increasing relevance because of ecological and economic reasons. The cultivation of maize in paddy soils during the dry season reduces water consumption and methane emissions, while fulfilling the increasing demand of maize for biofuel production and poultry fattening. However, introduction of upland crops in paddy fields often leads to carbon and nitrogen loss due to desiccation crack formation. Straw application can reduce crack formation and acts as fertilizer. The temporal dynamics of straw degradation under oxic conditions in paddy soils undergoing crop rotation have been scarcely studied. We identified the straw degrading microorganisms comparatively in the bulk soil and rhizosphere of maize by DNA-stable isotope probing with 13C-labelled rice straw and amplicon sequencing of the 16S rRNA gene and ITS1 region. Moreover, the degradation process in bulk soil was investigated over time. Straw degradation was performed by aerobic microorganisms and showed a clear temporal succession. In the initial phase, fast growing bacteria became labelled, followed by the labelling of fungi, known to degrade more complex carbon compounds. In the rhizosphere, partly different microorganisms were identified as labelled than in bulk soil, indicating that the microbial straw degradation process differs to some extent between these two compartments. The size of the labelled microbial population was smaller in the rhizosphere than in bulk soil, pointing to a preferential utilization of plant root derived carbon by microorganisms in the rhizosphere. •Microbial rice straw degradation undergoes a strong temporal dynamic.•bacterial degraders show a different dynamic compared to the fungal taxa.•Methanogens were not involved in rice straw degradation in oxic paddy soil.•Distinct microorganisms profit from rice straw in the rhizosphere than in bulk soil.•Rhizosphere microorganisms profit from rice straw in addition to root exudates.